CONSTANT EVALUATION OF COAL BULK CARRIER AS TECHNICAL DRAUGHT SURVEY SUPERVISION: A CASE STUDY AT COAL FIRED STEAM POWER PLANT - Denny Murdany Muchsin (TRAKSI, 2023)
The difference in cargo quantity between the results of the draught survey in Loading Port and Unloading Port is common thing in coal trading transactions. However, all parties (suppliers, buyers, and surveyors) agreed on a clause in adjusting the quantity of coal to be paid in case of a difference in a quantity exceeding 0.5%. However, the complicated draught survey process has the potential to cause anomalies in the final result. The anomaly existed once we compare precision of cargo quantity among ports with precision of bulk carrier constant among ports. This study aimed to confirm precision of bulk carrier constant be an alternative parameter in on-site supervision. The results of this study had proven that precision of cargo quantity cannot stand alone in on-site supervision. Precision of bulk carrier constant showed 77,6% of 75 shipments we exceed tolerance limit 10%.